WATER AND YOUR PROTECTION LEGAL INSTRUMENTS - Tamarindo, U. G. F.; Forti, J.C. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Brazil is naturally blessed with great rivers and vegetation in its territory, however, over the past decades, its greatest asset, fresh water, is being seriously compromised. It is a fact that the water was never very respected, perhaps because it is free and plentiful. However, the current situation of water scarcity in many regions of the country coupled with the misuse of land and other natural resources have produced, in addition to strong climate changes, major changes in the economy and society in general. Severe drought in the Southeast and Midwest regions of Brazil, as well as the excessive rains and floods in other parts of the country makes clear such a warning. Brazil is vulnerable to all these climate change. And in relation to water, there is no practical change in use will soon result in catastrophic for everyone. We cannot conceive the permanence of this current state of environmental inertia in relation to water. Current generations have an obligation to know and, above all, implementing the legal guardianship for the protection of ecosystems, especially water. And as Maude Barlow and Tony say Clarke, "is not soon change our relationship with water and ecosystems that remain, all our wealth and knowledge will have no meaning." National and international law establish safeguards to water, especially from the perspective that this can be a subject of rights. This article therefore presents an overview of the legal guardianship of protection to water.